Modelos de otimização para a cadeia de suprimentos de milho considerando mercado interno e exportação - Marins, Lara Beatriz Carvalho (Universidade Federal de São Carlos, 2021)
The Brazilian agroindustry has been notable for its economic importance to the country and the world. However, their geographical dispersion and the interference of biological and climatic factors imply complex production systems. Specifically, corn production involves an agroindustry production chain whose agents must prioritize in offering high quality products at a low cost in order to remain competitive in the market. In this work, two optimization models for tactical planning of production and logistics are proposed to assist in the analysis and decision-making process in the supply chain in corn agroindustry. The models can be useful to indicate and quantify alternatives to reduce costs or maximize the revenue and profit margins of the chain members, seeking the economic/operational efficiency of the chain and taking into account flow restrictions, capacities, inventory balancing and different types of demand in the chain. These linear optimization models consider the domestic market for animal consumption, ethanol production and international markets. They are mainly oriented to support policies and decisions of public agents who have some control and can interfere in almost the entire chain, such as government agricultural agencies and secretariats, instead of companies or private associations in the corn sector that operate in only part of the chain. These agents can interfere in the chain, for example, through incentives and investments in different production and transport capacities in the chain, through changes in legislation and taxes that affect the chain, among others. To verify the consistency of the models and validate this optimization approach, the models were implemented in an algebraic modelling language and solved by an optimization solver, using real data collected from various sources. The obtained results show the potential application of the models for these analyses and the importance of considering some aspects that have not been much studied in the literature, such as some opportunities to use different modes of corn distribution and some impacts of the Tax on Circulation of Goods and Services (ICMS) on its production and logistics systems. Other important aspects explored in the scenario analysis are the identification of capacity bottlenecks and investment opportunities in the chain. In addition, it shows the competitive situation of production in Brazilian states according to current production, logistics and policies, among others.
Modelos de optimización para la cadena de suministro de maíz considerando el mercado interno y de exportación
Keywords: Planejamento tático da produção e logística; Cadeia de suprimentos de milho; Otimização linear; Agroindústrias de milho; Gestão da cadeia de suprimentos; Pesquisa operacional; Tactical planning of production and logistics; Corn supply chain; Linear optimization; Corn agroindustry; Supply chain management; Operational research; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL